PENGARUH SENAM LOW IMPACT TERHADAP TEKANAN DARAH PRA LANSIA DENGAN HIPERTENSI DI PUSKESMAS SAIL KOTA PEKANBARU - Siska Mulyani; Apriyanto Apriyanto; Sri Yanti (Ensiklopedia of Journal, 2020)
Hypertension is one of the highest causes of death in people in the world. This disease is call silent killer. The prevalence of hypertension has reached 31.7% of the population in Indonesia. it increase because many factors such as genetics, less of physical activity and smoking. The purpose of this study was to see the effect of low impact exercise on pre-blood pressure in elderly with hypertension. This research was conducted on 12 respondents in Puskesmas Sail Pekanbaru.with bivariate. analysis this research is a quantitative with a quasi experimental design "pre and post test without control". with Wilcoxon test analysis. The results of this study showed that the average blood pressure before low impact exercise was 145.83 mmHg and after low impact exercise was 129.17 mmHg, while the average diastolic blood pressure before low impact exercise was 92.50 mmHg and the mean diastolic blood pressure after it was done impact low exercise is 81.67 mmHg. Based on the Wilcoxon test it can be concluded that there is the effect of low impact exercise in reducing systolic and diastolic blood pressure before and after low impact exercise with p value = 0.001 (systolic blood pressure) and p value 0,001 (diastolic blood pressure) (p = 0,05 ), it is recommended for further research to develop the effect of low gymnastics on the blood pressure of DM patients with hypertension.